Evaluation of Cord Blood biochemical parameters of term newborns in coastal parts of Odisha - Mantri, Santwana; Mohapatra, Prakash Chandra; Mishra, Pramila Kumari; Jena, Pradeep Kumar (Asian Journal of Medical Research, 2012)
Objective:Cord Blood parameters can be considered as early predictors of some of the metabolic disorders in future adult life. Based on this concept, our present observational study aims at evaluating the cord blood biochemical parameters & provides a concise view of their current status among the term newborns in coastal parts of Odisha. Methods:80 study participants were recruited as representative sample from coastal districts of Odisha after the careful sampling of cord blood. Demographic data related Questionnaire were translated into local language and administered to the mother individually. Processing of the blood samples and biochemical analysis of parameters were then carried out. Results:The Range of glucose & total protein level was found to be 39.8-95.92mg/dl, 5.07-7.65mg/dl. The Urea, Uric acid & Creatinine level were found to be in range of 13.21-25.79mg/dl, 3.03-7.45mg/dl, 0.629-1.19mg/dl respectively & compatible with reported level of other study. Total Cholesterol & Triglycerides level exhibited the Range of 27.74-89.66mg/dl, 24.28-81.12mg/dl. The level of High Density Lipoprotein, Low Density Lipoprotein and Very Low Density Lipoprotein was observed in the range of 6.66-23.54 mg/dl, 12.33-53.87 mg/dl, 4.82-16.18mg/dl respectively. The Range of total Alkaline phosphatase activity was observed to be lower to the level suggested by other investigators. But the level electrolytes like Na+, K+ were found to be lower in our study as compared to the level proposed by investigators of other study. Conclusion:We are concluding here that evaluation of cord blood parameters along with Alkaline phosphate activity, may help in providing a snapshot of health status as well as establishing the future Normal range for term newborns of Odisha.